Telepraca-zagrożenia, przed którymi stoją współpracownicy organizacji wirtualnej - Żukowska, Helena (Teleworking - threat before which stand the collaborator of virtual organization, 2006)
This article concentrates on teleworkers, starting from giving definition of telework. At the beginning l am presenting advantages and opportunities of telework focusing on disadvantages and threats waiting for teleworkers and other net users. The attention is drawn to the negative trend which is Internet addiction, pointing out its genesis as well as the types of personalities vulnerable to "netoholism".
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 677-685